Path Analysis on the Effect of Hormonal Contraceptive Use on the Risk of Depression in Women of Reproductive Age in Gunungkidul, Yogyakarta - Afriyanti, Neta; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: